Dietary supplementation of high-performance Canadian athletes by age and gender - Erdman, K. A.; Fung, T. S.; Doyle-Baker, P. K.; Verhoef, M. J.; Reimer, R. A. (Clinical Journal of Sport Medicine, 2007)
Objective: To determine dietary supplementation practices and opinions, preferred means for dietary supplement (DS) education, and antidoping opinions among elite Canadian athletes varying in age and gender.